A basic model of real-financial market interactions with heterogeneous opinion dynamics - Florian Hartmann; Matthieu Charpe; Peter Flaschel; Roberto Veneziani (Osnabrück University, Institute of Empirical Economic Research, 2016)
We consider an alternative modelling approach to the mainstream DSGE paradigm, namely a Dynamic Stochastic General Disequilibrium (DSGD) baseline model of continuous and gradual adjustment processes on interacting real and financial markets. Heterogeneous capital gain expectations (chartists and fundamentalists) are introduced in place of rational expectations and we show that the first type of agents tends to destabilise the economy. An additional feature is that the share of prevailing opinion types is able to switch endogenously. Global stability can be ensured if opinions favour fundamentalist behaviour far off the steady state. This interaction of expectations and population dynamics is bounding the potentially explosive real-financial market interactions, but can enforce irregular behaviour within these bounds when the dynamics is dominated by fundamentalist behavior far off the steady state (at least in the downturn). The size of output and share price fluctuations can be reduced however by imposing suitably chosen policy measures on the dynamics of the private sector.
Keywords: E12; E24; E31; E52; 330; output and share price dynamics; heterogeneous expectations; boundedness; persistent irregular fluctuations; policy measures